Análise da suscetibilidade a incêndios por meio de geoprocessamento : um estudo no município de Ribeirão Preto, SP - Neves, Luiza de Lima (Universidade Federal de São Carlos, 2017)
Fires are among the main environmental problems in Brazil. The country is considered one of the great potentials for the increase of greenhouse gases in the planet coming from the emissions of the burning of vegetal biomass. According to IBAMA, besides contributing to global warming and climate change, fires also pollute the air, cause economic and social damage and accelerate the desertification processes, as well as the deforestation and loss of biodiversity. In the city of Ribeirão Preto (SP), this is a problem that has been aggravating in recent years, mainly due to the recent and long periods of drought, religious ritual practices in the nearby forest and the extensive cultivation of sugarcane in the region. In order to analyze a fire occurrence and susceptibility, different methodologies can be adopted. One of them refers to the use of geoprocessing, which encompasses a series of tools that are of great importance for the collection and analysis of physical information related to geographic space, mainly through geographic information systems (GIS) and remote sensing. They make possible to study large areas quickly and objectively, and allow the interaction between different types of data. Through these tools, this paper aims to analyze the fire outbreaks susceptibility in the mentioned municipality through the identification, survey and weighting of previously established geographical indicators. The proposal of a new model sought to advance the existing methodologies through the inclusion of temporal variation in the study, as well as the use of vegetation indices with medium spatial resolution. The results indicate that the model is efficient for a fire susceptibility analysis, but is substantially dependent on data availability and continuous updating. The final maps emphasize the importance of each indicator and stress the need to explore the temporal variation in the study.
Analysis of the susceptibility to fire using geoprocessing tools : a study in the municipality of Ribeirão Preto - SP
Keywords: Suscetibilidade a incêndios; Análise ambiental; Sensoriamento remoto; SIG; Fire susceptibility; Environmental analysis; Remote sensing; GIS; CIENCIAS EXATAS E DA TERRA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::FOTOINTERPRETACAO FLORESTAL